‘Systems of values’, ‘ethical systems’, and sustainability. The economic social ‘entity’ values - Galassi, Giuseppe (De Computis, Revista Española de Historia de la Contabilidad., 2021)
The paper aimsto explore the relationships between ‘ethical systems’ and ‘systems of values’, offering also semantic and epistemological issues from which ethics cannot be divorced. Although ethics is a branch of philosophy that has its roots in ancient Greece, it experienced a remarkable revival in recent decades not only in philosophy but also in the social and applied sciences. And this deserves wider recognition and appreciation. A considerable amount of ethical thinking can be found in the current and previous literature of economia aziendale, entity economics, general economics, management, and social philosophy. Ethical principles are coextensive with principles of rational behavior and all ethics are contextual in the sense that surrounding circumstances, environmental conditions and situations are involved. The reference to science and mathematics for ethical arguments partially depends on methodology based on a postulated outside ‘natural world’ with statistical relative uniformities. Behavioral economists and management scientists prefer, as primitive foundations, scientific methods with their observations and prediction of economic and sociological relative regularities. The ‘received view’ that language itself conditions all aspects of reality includes now the topic that persuasion and rational arguments can support ‘ethical systems’. Realization of common welfare is a prerequisite for establishing a ‘master values system’ and for meeting the ‘specifics’ which compose ethical principles. The historical research and anthropological analysis are necessary for constructing suitable ‘system of values’ for every entity, economic and not. The coordination of specific ‘systems of values’ and directives is a necessary condition for social welfare. Consequently, any society must compose every kind of conflicting ‘values systems’ and ends into a coherent framework. Neoclassic economics traditionally neglected ‘environmental and social issues’. Different variations of environmental ethics have been developed; beyond many questions, there are the issues of cause and remedy of the global as well as local ecological crisis. To-day, in times of crisis and pandemia the market paradigm is exhausted, it does not meet the ‘ethics of reciprocity’. In socialist economics exchanging goods at their ‘socially necessary labor cost’ would operate as a satisfactory surrogate. Also, entity economics does not completely escape the labor value identification of classical economics.